The Mediating Role of Trust in the Relationship Between Information Quality, Corporate Image, and Loyalty - I Kadek Budi Astawan; Pande Ketut Ribek; I Gusti Ayu Imbayani; Nengah Landra (International Journal of Applied Business and International Management, 2025)
Continuous engagement in long-term healthcare programs such as the Back-Referral Program (Program Rujuk Balik or PRB) depends on sustained participant loyalty, which is shaped by service-related perceptions and psychological factors. Previous studies have highlighted the roles of information quality and corporate image in influencing participant behavior; however, inconsistencies remain regarding their direct effects on loyalty. This study examines the influence of information quality and corporate image on customer loyalty, with trust considered as a mediating variable. Using a quantitative approach, data were collected from 271 PRB participants and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that information quality does not have a direct effect on loyalty (? = 0.082; p 0.05) but contributes positively to trust (? = 0.463; p 0.001). Corporate image shows a significant direct effect on loyalty (? = 0.209; p 0.05) and also enhances trust (? = 0.488; p 0.001). Trust demonstrates a strong positive effect on loyalty (? = 0.521; p 0.001) and serves as a mediating mechanism linking information quality and corporate image to loyalty outcomes. These findings highlight the importance of trust in maintaining long-term engagement in public healthcare programs and suggest that clear communication, reliable service delivery, and a credible institutional image are central to fostering participant loyalty.